Gambaran Diagnosis dan Intervensi Keperawatan Kerusakan Integritas Kulit pada Masyarakat Terdampak Banjir di Kalimantan Selatan - Aridamayanti, Bernadetta Germia; Yakin, Rahimul; Nisvia, Nathasya; Asiah, Nor; Putra, M. Aditya; Lathifa, Yulin (FORIKES, 2024)
Floods carry disease-causing microorganisms. The danger of E-coli and Leptospira bacteria tends to increase after flooding. This causes skin diseases that threaten health. Skin disease nursing problems, found in NANDA: International Nursing Diagnosis. However, until now there has been no nursing research regarding nursing diagnosis, intervention for damage to skin integrity and its implementation in flood-affected communities. The aim of this research was to describe the characteristic limits, related factors and nursing intervention from the nursing diagnosis of damage to skin integrity. This type of research was a descriptive study involving 170 respondents selected using consecutive sampling technique. The data collection instrument was a nursing diagnosis questionnaire sheet: damage to skin integrity based on